Advances in mRNA Vaccines for Infectious Diseases - Zhang, Cuiling; Maruggi, Giulietta; Shan, Hu; Li, Junwei (Frontiers in Immunology, 2019)
During the last two decades, there has been broad interest in RNA-based technologies for the development of prophylactic and therapeutic vaccines. Preclinical and clinical trials have shown that mRNA vaccines provide a safe and long-lasting immune response in animal models and humans. In this review, we summarize current research progress on mRNA vaccines, which have the potential to be quick-manufactured and to become powerful tools against infectious disease and we highlight the bright future of their design and applications.